Consider Long-term Implications Now and Forever. (Communications of the ACM, 2004)
Presents letters to the editor about information technology, published in the journal "Communications of the ACM." Comment by Scott Ambler on the article "Optimistic Optimization" by Peter G. Neumann, concerning a problem in the information technology industry involving the failure of developers to consider the long-term implications of their decisions, that was previously published in the journal; Agreement of Newmann with Ambler on his comments.